KARTAGENER’S SYNDROME AND ACUTE APPENDICITIS - Kashif, Ali; Masud, Mannan; Manzoor, Syed Mohsin; Haneef, Saqib (Journal of Ayub Medical College Abbottabad, 2010)
Kartagener’s syndrome is a combination of situs inversus totalis, sinusitis and bronchiectasis. Left sided appendicitis can present with problems in diagnosis and during surgery. We present here a case of Kartagener’s syndrome and left sided appendicitis successfully managed in a peripheral hospital in Bahawalnagar, Pakistan. Keywords: Kartagener’s syndrome, Situs Inversus Totalis, Left sided appendicitis